Readymade-image-sentence: protest aesthetics in a time of democracy post-1989 - McInneny, Anthony (Design/Arts/Culture, 2022)
ABSTRACT Jacques Rancière perceives the image as what is sayable and visible and 20C film montage as an Image-sentence: the closest proximity of parallel realities (Rancière 2007). Prohibited from public view, Marcel Duchamp’s 1917 Readymade revolution is re-membered in a photographic image: a fountain-urinal. On the mourning after WWII, George Orwell noted readymade-sentences of what could(n’t) be said (Duchamp 1997). Captured by Rene Magritte, the treachery of a painted-word-image-thought, could have been a film about what it wasn’t (Flavia, 2014). About now, Walter Benjamin saw an optical unconscious in the photograph miraculously inverting the awe of culture and nature. (Benjamin 2004) After 1989, Bruno Latour held this modern Constitution as equally anti-modern (before ever having been modern) and postmodern, after which there would be nothing, except the digital image (Latour 1993). Before this, Situationist International and Fluxus showed life as the other side art. Keep your coins, I want change, read millennial graffiti’s signature anonymity . With no True North, this portfolio-essay presents an Image of protest aesthetics in a time of democracy post-1989. Before, from a North in the South; after from southern hemisphere parallels; in-between from a South in the North. Overarching is a Pacific mirror. Each readymade-image-sentence has four cartoons and four, 200-word max. abstract captions. Keywords – aesthetics, protest, city, North-South, East-West